MEASURING THE LEVEL OF USER SATISFACTION OF SITENOR WEB-BASED APPLICATIONS USING THE USABILITY SCALE SYSTEM - nggara, feri; F. Antonius A (STKIP Muhammadiyah Kuningan, 2023)
The use of applications in government agencies has become a necessity for acceleration to help carry out various tasks. The SITENOR application developed by the Ministry of Youth and Sports in the field of sports personnel is designed as an effort to develop performance through the use of technology. The method used is descriptive survey analysis using the System Usability Scale (SUS). The analysis results show that the SUS SITENOR satisfaction survey score is 78, which is in the good category. This means that the SITENOR application can be accepted and is good for use in the Ministry of Youth and Sports